2018
DOI: 10.3390/ijerph15040790
|View full text |Cite
|
Sign up to set email alerts
|

Association between Body Image Dissatisfaction and Self-Rated Health, as Mediated by Physical Activity and Eating Habits: Structural Equation Modelling in ELSA-Brasil

Abstract: This study investigated whether the association between body image dissatisfaction and poor self-rated health is mediated by insufficient physical activity and unhealthy eating habits. The participants were 6727 men and 8037 women from the baseline (2008–2010) of the Longitudinal Study of Adult Health (Estudo Longitudinal de Saúde do Adulto, ELSA-Brasil). Structural equation modelling was used. Associations were found between body image dissatisfaction and poor self-rated health in both sexes. Insufficient phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 45 publications
4
9
0
2
Order By: Relevance
“…SE and body shape concern. Earlier studies often had a crosssectional design [26,27], however, and our findings add support for the mutual and reciprocal link over time between SRH and SE. We also revealed that both SRH and SE were associated with a leaner body after the 2 years.…”
Section: Discussionsupporting
confidence: 78%
“…SE and body shape concern. Earlier studies often had a crosssectional design [26,27], however, and our findings add support for the mutual and reciprocal link over time between SRH and SE. We also revealed that both SRH and SE were associated with a leaner body after the 2 years.…”
Section: Discussionsupporting
confidence: 78%
“…SE and body shape concern. Earlier studies often had a cross-sectional design (26,27), however, and our ndings add support for the mutual and reciprocal link over time between SRH and SE.…”
Section: Main Ndingssupporting
confidence: 63%
“…For women, selfreported eating assessment and body image importance were significant, corroborating previous results. 36,37 This finding highlights the relevant role that eating can play in an individuals' body appearance. The significant paths between economic class and body image have been reported in previous studies, 17 illustrating how individuals with greater economic power are more dissatisfied with their body and may engage more often in strategies to seek body change.…”
Section: Resultsmentioning
confidence: 73%